Co-digestion of mixed sewage sludge and fruit and vegetables wastes effect of different mixtures on biogas yield - Arhoun, Brahim; Gómez-Lahoz, César; Rodríguez-Maroto, José Miguel; García-Herruzo, Francisco; Vereda-Alonso, Carlos (My University, 2015)
Disposal of fruit and vegetable wastes (FVWs) in landfill site cause serious environmental issues such as contamination of soil, air and ground water. These wastes contain large quantities of biodegradable organic fractions, with high moisture that facilitates their biological treatment. One of the best alternatives to landfill disposal of these wastes is the anaerobic digestion. Therefore, it is one of the most widespread stabilization processes of the sludge in municipal wastewater treatment plants (WWTP). Introduction of FVW in WWTP and co-digestion with mixed sludge (MS) could enhance biogas production and plant economic feasibility. A lab-scale experiment for the anaerobic co-digestion of FVW and municipal mixed sludge under mesophilic condition and 20 days hydraulic retention time is investigated. Initially the digester was fed with mixed sludge (MS) from wastewater treatment plants with an average organic loading rate (OLR) of 0.63 (g L–1 d–1). The co-digestion of mixed sludge and FVW was performed at various organic loading ratios (OLRs), between 0.63 and 5.5 (g L–1 d–1). The experimental specific biogas and methane productions are 0.656 L g–1 and 0.340 L g–1 respectively. Alkalinity and pH remains relatively constant regardless the introduction of different proportions of FVW in the mixture. Co-digestion, compared with the digestion of MS as single substrate, improves the biogas and methane production.
Keywords: Biogas; Co-Digestion; Sewage; Sludge; Fruit and vegetable wastes